Analysis of The Urban Space Perception, Transformed Under the Influence of Complementary Architecture. (2016) - Wojciuk, Natalia; Milwicz, Roman; Nowotarski, Piotr
Abstract: The character of urban space is being recreated by changes, which are taking place very fast. Especially buildings that are a part of the complementary development have an important influence on its composition. With the penetration into the historical and compact urban fabric, the complementary buildings are transforming the face of well-known places that often have a rich history which was permanently inscribed in the memory of the inhabitants of many generations. Authors of this article have selected an example of public space in Poznan and Wroclaw, which metamorphosed within the last 10 years and analyzed the way of engaging dialogue with the modernity. The review of the metamorphosed spaces was made in the light of architectural, conservation and psychological aspects that allows pointing the key of successful building.